Nursing Students’ Opinions About the COVID-19 Vaccine: A Descriptive, Cross-Sectional Study - Köse, Selim (SAKARYA ÜNİVERSİTESİ, 2022)
Objective: This study aims to identify the nursing students' opinions about the COVID-19 vaccine. Materials and Methods: This descriptive, cross-sectional study was realized with 1008 students enrolled in the nursing departments of four universities located in Istanbul. Data were collected online with Information Form. Results: 85.7% of the students did not get a COVID-19 vaccine, and 44.8% of the unvaccinated students did not think about getting a vaccine or were indecisive. The reasons for the students' not thinking about getting the vaccine or their indecisiveness about it were most frequently the vaccine having been produced in a very short time, not trusting the protection or content of the vaccine, not having enough information about the vaccine. A significant difference was found between the students’ grade (p= 0.000), type of university (p= 0.000), knowledge level about the COVID-19 illness (p= 0.028) and vaccine (p= 0.000) and their thinking about getting vaccinated. Conclusion: It was found that a tiny part of the students was vaccinated; almost half of the unvaccinated students did not think about getting vaccinated or were indecisive. Understanding the student's perspective on the COVID-19 vaccine can be helpful in planning multidisciplinary education strategies.
Keywords: COVID-19 vaccines; immunization; nursing; vaccination